2014
DOI: 10.1111/head.12503
|View full text |Cite
|
Sign up to set email alerts
|

Pain Beliefs and Perceptions Inventory: A Cross‐Sectional Study in Chronic and Episodic Migraine

Abstract: This is the first study, to our knowledge, that addresses differences and predictive factors in pain beliefs according to headache diagnosis. A deeper knowledge of beliefs pattern in patients could lead to better-tailored psychological management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
6
1
1
Order By: Relevance
“…The present study demonstrated that MBCT could not be useful in pain beliefs, which is not consistent with the previous studies [26,27,33,34]. A possible explanation is that the pain beliefs and perceptions inventory only assesses one aspect of pain namely cognitive or psychological aspect.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The present study demonstrated that MBCT could not be useful in pain beliefs, which is not consistent with the previous studies [26,27,33,34]. A possible explanation is that the pain beliefs and perceptions inventory only assesses one aspect of pain namely cognitive or psychological aspect.…”
Section: Discussioncontrasting
confidence: 96%
“…Pain beliefs and perceptions inventory has 16 items that was constructed by Williams and Thorn [26,27]. The inventory assesses three dimensions of pain beliefs; 1.…”
mentioning
confidence: 99%
“…Research on chronic pain (CP) indicates that low levels of maladaptive pain beliefs are combined with adaptive coping skills, which in turn lead to better psychosocial and physical functioning (Morgan, 2013;Walsh & Radcliffe, 2002). Nevertheless, usually CP patients have maladaptive mental representations of pain as persistent and mysterious, which are associated with poor adaption to pain as well as to psychosocial and physical dysfunction (Condello et al, 2015;Dysvik, Lindstrøm, Eikeland & Natvig, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that catastrophizing interferes with pain-related coping and health behaviors, such that, even when individuals with high levels of catastrophizing use coping strategies, they are less efficient in reducing pain (Condello, et al, 2015;Edwards et al, 2011). Coping is one of the most frequently used concepts related to the behavioral strategies used to control stress (Bussing, Ostermann, Neugebauer & Heusser, 2010;Lazarus, 1993;Tan, Teo, Anderson & Jensen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Others have assessed selfblame for other aspects of the illness experience rather than its cause or onset (e.g., treatment ineffectiveness) (Aguado Loi et al, 2013;Bussell & Naus, 2010;DePalma, Rollison, & Camporese, 2011;Ibrahim, Chiew-Thong, Desa, & Razali, 2013;McSorley et al, 2014) or have measured a general tendency to experience self-blame outside of the illness context (Ali et al, 2000;Rich et al, 1999). Some have also assumed self-blame from measures that do not separate self-blame for illness onset from other related but potentially distinct constructs, such as a tendency to self-criticize or harbour feelings of guilt or shame (Condello, Piano, Dadam, Pinessi, & Lanteri-Minet, 2015;Else-Quest et al, 2009;Hommel et al, 2000;Karlsen & Bru, 2002). Some researchers have argued that these 'self-conscious emotions' naturally follow, and can therefore evidence, self-blame (Kubany & Watson, 2003).…”
Section: Introductionmentioning
confidence: 99%